DFT computational study of the tetragonal (P4/nmm) WO 3 (001) Surface. (2018)
(Eng) Tetragonal WO 3 is important for catalytic reactions such as the hydration of ethylene, which is an alternative choice to ethanol production by fermentation. However, very little is known about the structural and electronic properties of the tetragonal WO 3 surfaces with possible catalytic activity. In this work, the WO 3 (001) surface was characterized by means of density-functional-theory computer simulations. The crystal unit cell parameters and the corresponding angles and bond distances were determined, and the density of states (DOS) for the bulk was calculated. The band gap turned out to be 0.6 eV. Two (001) surface models were generated, one without oxygen atoms at the surface (model I) and the other with only one oxygen atom at the surface (model II). For both models, four converged layers of atoms and a vacuum of 14 Å between neighboring slabs were used for the calculations. Values of 135.01 and 40.55 meV/ Å 2 for the surface energies of models I and II, respectively, were obtained, showing that model II is more likely to represent the WO 3 catalyst. The density of states (DOS) was calculated for each surface model, and both of them exhibited an energy gap close to zero.